2022
DOI: 10.3390/pathogens11091013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Avian Influenza Viruses Isolated from the Izumi Plain, Japan in 2019/20 Winter Season

Abstract: The Izumi plain in the Kagoshima Prefecture, Japan, is known as an overwintering site for more than 30,000 migratory waterfowl, including endangered crane species. We previously reported that environmental water samples, from artificial wet paddies created as crane roost sites on the Izumi plain, are useful for avian influenza virus (AIV) surveillance. During the 2019/20 winter season, we collected 238 water samples from the crane roost sites and isolated 22 AIVs of six subtypes: one H1N1, one H3N2, seven H3N8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Genetic analyses of the H3 HA genes revealed that the H3 AIVs could be classified into three genetic clades: H3-I to H3-III (). Genetic clade H3-I included H3N8 AIVs isolated during the 2019/20 winter season [18]. All the H3N6 and H3N8 AIVs, with the exception of A/environment/Kagoshima/KU-C12/2020 (H3N6) and A/environment/Kagoshima/KU-J6/2020 (H3N6) that belonged to clade H3-II, were classified under genetic clade H3-I.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic analyses of the H3 HA genes revealed that the H3 AIVs could be classified into three genetic clades: H3-I to H3-III (). Genetic clade H3-I included H3N8 AIVs isolated during the 2019/20 winter season [18]. All the H3N6 and H3N8 AIVs, with the exception of A/environment/Kagoshima/KU-C12/2020 (H3N6) and A/environment/Kagoshima/KU-J6/2020 (H3N6) that belonged to clade H3-II, were classified under genetic clade H3-I.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated the viral transition of AIVs among wild waterfowl overwintering in Kagoshima prefecture during the 2020/21 winter season. We isolated the highest number of AIVs in the 2020/21 winter season in our AIV surveillance since the 2012/13 winter season [13,14,18,21,22]. Due to the high number of AIV-positive samples found in crane roost water during the 2020/21 winter season, we developed real-time RT-PCR methods to distinguish samples containing multiple HA subtypes of AIVs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations